A low recombination rate indolizine sensitizer for dye-sensitized solar cells. Issue 54 (15th June 2016) - Huckaba, Aron J.; Yella, Aswani; Brogdon, Phillip; Scott Murphy, J.; Nazeeruddin, Mohammad Khaja; Grätzel, Michael; Delcamp, Jared H.
Abstract : A novel indolizine donor for DSC use with an extended absorption spectrum shows good voltages and enhanced short circuit current. Abstract : A sensitizer incorporating a heavily alkylated surface blocking indolizine donor exhibits excellent light absorption and diminished recombination rates in dye-sensitized solar cells (DSCs). DSC device efficiencies (up to 8%) using either I − /I3 − or Co(bpy)3 2+/3+ redox shuttles were obtained, which compare favourably to the known excellent surface coverage co-sensitization dye, D35 .